A role for the age‐dependent loss of α(E)‐catenin in regulation of N‐cadherin expression and cell migration - Nichols, LaNita A. (Wiley Periodicals, Inc., 2014)
The aging kidney has a decreased ability to repair following acute kidney injury. Previous studies from our laboratory have demonstrated a loss in α‐catenin expression in the aging rat kidney. We hypothesize that loss of α‐catenin expression in tubular epithelial cells may induce changes that result in a decreased repair capacity. In these studies, we demonstrate that decreased α‐catenin protein expression is detectable as early as 20 months of age in male Fischer 344 rats. Protein loss is also observed in aged nonhuman primate kidneys, suggesting that this is not a species‐specific response. In an effort to elucidate alterations due to the loss of α‐catenin, we generated NRK‐52E cell lines with stable knockdown of α(E)‐catenin (C2 cells). Interestingly, C2 cells had decreased expression of N‐cadherin, decreased cell–cell adhesion, and increased monolayer permeability. C2 had deficits in wound repair, due to alterations in cell migration. Analysis of gene expression in the migrating control cells indicated that expression of N‐cadherin and N‐CAM was increased during repair. In migrating C2 cells, expression of N‐CAM was also increased, but the expression of N‐cadherin was not upregulated. Importantly, a blocking antibody against N‐cadherin inhibited repair in NRK‐52E cells, suggesting an important role in repair. Taken together, these data suggest that loss of α‐catenin, and the subsequent downregulation of N‐cadherin expression, is a mechanism underlying the decreased migration of tubular epithelial cells that contributes to the inability of the aging kidney to repair following injury.